Relevance of ‘urf to Mahar: The Marriage Traditions of the Buton Tribe - Maulana, Adri (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2025)
The tradition of determining the dowry in traditional Butonese marriage reflects the strong relationship between local cultural values ​​and the application of Islamic Law. Custom (‘urf) in determining the amount of dowry are often influenced by social class. The relationship between the traditional practice of determining the amount of the dowry and social class is studied from the perspective of Ushul Fiqh, especially rules of ‘urf shahih and maqāṣid al-syarī’ah. Data was obtained from literature study and analysis of customary norms. The results of the study show that the application of dowry adjustments according to social status can be justified as long as it does not conflict with the principles of justice and does not cause harm. ‘Urf functions as a source of contextual law and can strengthen sharia values ​​if it is regulated by taking into account benefits. The results of the study are discussed in the context of preserving cultural traditions in Buton which is in accordance with the main objectives of Islamic Law.